Comparison of Hyperpolarization-Activiated Current “if ” on the Rate of Spontaneous Activity and Cycle Length before and after Cutting of Atrial Muscle away from Intact Sinoatrial Node of Rabbit - M.R Nikmaram,; M.R Boyett,; H Fathimoghaddam, (Journal of Kerman University of Medical Sciences, 2003)
It has been shown that the hyperpolarization-activated current “if” that is blocked by 2 mM Cs+ plays a minor role on pacemaker activity of the center and a major role on activity of the periphery of rabbit intact sino-atrial node. On the other hand some investigations showed that if the atrial muscle, surrounding the sino-atrial node, is cut away there is a shift in leading pacemaker site from the center to the periphery and an increase in the rate of spontaneous action potentials.This can be explained by the loss of the electrotonic suppression of the node periphery by the atrial muscle or the greater role of “if” current on peripheral zone. 2mM Cs+ decreased the rate of spontaneous activity by 13±2 % before the cutting whereas after cutting it decreased the rate by 20±4%. This can be explained by the shift in leading pacemaker site from the center to the periphery after the cutting. It is possible to conclude that increase in rate of spontaneous activity after cutting is the result of the greater role of “if” current in peripheral zone.